PRIVATE OR PUBLIC ACCOUNTING. - Byrnes, Thomas W. (The Accounting Review, 1946)
Abstract This article focuses on the private or public accounting. Colleges offering courses in accounting have lately been besieged by applicants for admission. For the most part those desiring to enroll are honorably discharged veterans whose educational programs were interrupted by induction into the services. Among those accepted many are taking refresher courses and all are faced with the perplexing problem of choosing sooner or later between a position in the accounting division of a business, institutional, or governmental activity and a career in public accounting. Any statement regarding the advantages and disadvantages of the two accounting fields must be related to the temperament dandy the ultimate goal of the aspirant In business organizations accountancy-trained persons find their principal work opportunities in positions leading to cost accountant, internal auditor, chief accountant, credit executive, controller, and treasurer. In governmental departments investigative accountants, tax auditors, and analysts are in demand. The ultimate vocational opportunity in practice is that of staff supervisor and principal.